2015
DOI: 10.1007/978-1-4939-2257-4_30
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Mitochondrial Protein Glutathionylation as Signaling for CO Pathway

Abstract: Protein glutathionylation is a posttranslational process that regulates protein function in response to redox cellular changes. Furthermore, carbon monoxide-induced cellular pathways involve reactive oxygen species (ROS) signaling and mitochondrial protein glutathionylation. Herein, it is described a technique to assess mitochondrial glutathionylation due to low concentrations of CO exposure. Mitochondria are isolated from cell culture or tissue, followed by an immunoprecipitation assay, which allows the captu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Interestingly, 14 CO 2 production from [3,[4][5][6][7][8][9][10][11][12][13][14] C]glucose and [6-14 C]glucose did not change with serotonin treatment, whereas decarboxylation of [1-14 C]glucose rose considerably. Presumably, the net rise in shunt flux determined with [1-versus 6-14 C]glucose also involves [3,[4][5][6][7][8][9][10][11][12][13][14] C]glucose with its label scrambling via the shunt. Ignoring Fru-6-P recycling, the rise in glycolysis during serotonin treatment might be roughly estimated by dividing the net rise in shunt flux rate in Table II 3 H can also be transferred to other compounds, such as fatty acids and glycerol in rat epididymal fat pad slices (337), reducing the amount in water.…”
Section: Pentose Phosphate Shunt Pathway: Oxidative Stress Management and Biosynthesismentioning
confidence: 97%
See 4 more Smart Citations
“…Interestingly, 14 CO 2 production from [3,[4][5][6][7][8][9][10][11][12][13][14] C]glucose and [6-14 C]glucose did not change with serotonin treatment, whereas decarboxylation of [1-14 C]glucose rose considerably. Presumably, the net rise in shunt flux determined with [1-versus 6-14 C]glucose also involves [3,[4][5][6][7][8][9][10][11][12][13][14] C]glucose with its label scrambling via the shunt. Ignoring Fru-6-P recycling, the rise in glycolysis during serotonin treatment might be roughly estimated by dividing the net rise in shunt flux rate in Table II 3 H can also be transferred to other compounds, such as fatty acids and glycerol in rat epididymal fat pad slices (337), reducing the amount in water.…”
Section: Pentose Phosphate Shunt Pathway: Oxidative Stress Management and Biosynthesismentioning
confidence: 97%
“…An in vivo approach is to inhibit 6-phosphogluconate dehydrogenase and measure the rate of incorporation of 14 C into 6-phosphogluconate from [U-14 C]glucose over short time intervals (205). More recent MRS assays in vitro and in vivo include use of [2-or 3- 13 C]glucose (67), [1,[2][3][4][5][6][7][8][9][10][11][12][13] C 2 ]glucose (66,183), and [1,[6][7][8][9][10][11][12][13] 532) provided evidence for recycling of Fru-6-P back to Glc-6-P via PGI and re-entry into the shunt (FIGURE 1). They showed that when pentose shunt activity measured as 14 CO 2 production from ( 14 C 1 -14 C 6 )glucose and was reduced by 50% with dehydroepiandrosterone (DHEA) to inhibit 6-phosphogluconate dehydrogenase, there was a twofold increase in 3 H 2 O release from [3-3 H]glucose (ascribed to glycolysis, but see below) and a 3.5-fold rise in [Glc-6-P].…”
Section: Pentose Phosphate Shunt Pathway: Oxidative Stress Management and Biosynthesismentioning
confidence: 99%
See 3 more Smart Citations